An Innovative and Time Efficient Approach to Secure Text Data Specifically on Cloud Environment - Shah, Ankur N.; Dahiya, Vishal; Dave, Jay A. (International Journal of Membrane Science and Technology, 2023)
Data security is highly vital and crucial for every organization, regardless of size of organization—whether it it is a small scale organization, medium scale organization, or large scale organization. This applies to the both inside and outside the organization. The essential prerequisite for anyone's confidence and trust in any organization is data security. In day to day life human generates various data in different formats like text data, graphical data, voice data, video data etc. using various medium like youtube, twitter, facebook, instragram, emails etc. These data may be a structural data, may be a semi structural data or may be an unstructured data. In today’s life all the data which are generated is generally huge in size which we termed as big data. To handle this big data is very difficult task. Cloud computing is one of the technique which can handle this very well. But the main fact is that there are various challenges to both of these technologies. One of the biggest challenges is to provide security to this kind of data. There are various research has been done and still going on to address this issue effectively. In this paper we have also tried to address this issue after doing exhaustive literature work then we provide our own AVJ security algorithm which can provide security to text data. The writers' names—A for Mr. Ankur Shah, V for Dr. Vishal Dahiya, and J for Dr. Jay A Dave—led to the creation of the moniker AVJ***Throughout this paper we have used term base paper algorithm meaning that we are using reference paper [5] algorithm of Mohammad Anwar Hossain and et al.